Solubility of Structurally Complicated Materials: 3. Hair - Ari L. Horvath (The Scientific World Journal)
Hair is composed of proteins, lipids, water, and small amounts of trace elements. All proteins in animal and human bodies are built from permutations of amino acid molecules in a polypeptide string. The polypeptide chains of protein keratin are organized into filaments in hair cells. Hair is one of the most difficult proteins to digest or solubilize. Among the most common dissolving procedures for hair are acidic, alkaline, and enzymatic hydrolysis. For the analysis of hair, the solid samples are transferred by solubilization via digestion into a liquid phase. Small molecular solvents and molecules with hydrophobic groups appear to have higher affinity for hair. A good solvent attacks the disulfide bonds between cystine molecules and hydrates the hair shaft. Consequently, the hair becomes a jelly-like mass.